Insights into the photochemistry of 5-aminotetrazole derivatives with applications in coordination chemistry. Effect of the saccharyl moiety on the photostability - Ismael, Amin (2021)
The properties and applications of 2-methyl-(211)-tetrazole-5-amino-saccharinate (2MTS) in catalysis and chelant-based chemotherapy stimulated investigations on its photostability. The photochemistry of monomeric 2MTS in solid argon (15 K) was compared with those of 2-methyl-(2H)-tetrazole-5-amine (2MT) and 1-methyl-(2H)-tetrazole-5-amine (1MT). Compounds were subjected to in situ narrowband UV-irradiation at different wavelengths. Reactions were followed by infrared spectroscopy, supported by B3LYP/6-311++G(d,p) calculations. Photochemical pathways for 2MT and 2MTS proved similar but photodegradation of 2MTS was 20x slower, unraveling the photostabilizing effect of the saccharyl moiety that extends into the nitrilimine formed from 2MTS and its antiaromatic 1H-diazirene isomer, which proved photostable at 290 nm, unlike the 1H-diazirene formed from 2MT. Analysis of the photochemistries of 2MTS/2MT (250 nm) and 1MT (222 nm), including energy trends calculated for the isomeric C2H5N3 species postulated/observed from photolysis and EPR results, enabled a deeper insight into the photodegradation mechanisms of 1,5-substituted and 2,5-substituted tetrazoles. We postulate a pivotal singlet state imidoylnitrene species, (s)N1, as common intermediate, which undergoes a Wolff-type isomerization to a stable carbodiimide. Photo-extrusion of N-2 from 1,5-substituted tetrazoles generates (s)N1 directly but from 2,5-substituted tetrazoles it originates a nitrilimine, then a diazirene, which finally leads to (s)N1. Selective formation of cyanamide from 1MT requires photoisomerization between (s)N1 and (s)N2, accessible at 222 nm. EPR studies enabled the detection of methyl nitrene, arising from photolysis of 1H-diazirene intermediate.